2014
DOI: 10.3201/eid2011.140556
|View full text |Cite
|
Sign up to set email alerts
|

Poultry Market Closures and Human Infection with Influenza A(H7N9) Virus, China, 2013–14

Abstract: Closure of live poultry markets was implemented in areas affected by the influenza virus A(H7N9) outbreak in China during winter, 2013–14. Our analysis showed that closing live poultry markets in the most affected cities of Guangdong and Zhejiang provinces was highly effective in reducing the risk for H7N9 infection in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 11 publications
(11 reference statements)
3
45
0
1
Order By: Relevance
“…Population contact with live poultry decreased in influenza A(H7N9) virus–affected and –nonaffected areas after cases were detected in China, although exposure to live poultry in urban and rural areas remained high in the country ( 12 ). Live poultry markets in China, particularly in cities, have been closing either temporarily or permanently since the first wave in 2013 ( 2 , 13 ). Some cities severely affected by influenza A(H7N9) virus in the Yangtze River Delta permanently closed all live poultry markets in 2014, which led to a substantial decline in population exposure to the virus and the risk for infection.…”
Section: Discussionmentioning
confidence: 99%
“…Population contact with live poultry decreased in influenza A(H7N9) virus–affected and –nonaffected areas after cases were detected in China, although exposure to live poultry in urban and rural areas remained high in the country ( 12 ). Live poultry markets in China, particularly in cities, have been closing either temporarily or permanently since the first wave in 2013 ( 2 , 13 ). Some cities severely affected by influenza A(H7N9) virus in the Yangtze River Delta permanently closed all live poultry markets in 2014, which led to a substantial decline in population exposure to the virus and the risk for infection.…”
Section: Discussionmentioning
confidence: 99%
“…While influenza virus may be transmitted among humans via fomites, droplets, or aerosols (28), the mode of H7N9 transmission remains unclear. Closure of live-poultry markets was effective in temporarily reducing human cases (29)(30)(31), but close to 200 human infections were reported during the winter of 2014-2015, with a wider geographic distribution to Xinjiang and Jilin in 2014 (1). While chicken is the most common species in the live-poultry markets harboring the H7N9 virus (6,32,33), the predominant mode that facilitates the spread of H7N9 virus among poultry is also not fully understood.…”
mentioning
confidence: 99%
“…Closure of LPMs was conducted to block the transmission of H7N9 and has been considered as the most effective method for restricting the epidemic to date in China 3, 11, 17. Zhejiang Province closed all LPMs in central urban areas concerning the high incidence of H7N9 cases in July 2014, prior to the third wave.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data suggested that avian influenza A(H7N9) infections were associated with exposure to live poultry markets (LPMs) 2, 3, 4, 5, 6. To control its impact, temporary or permanent closure of live poultry markets has been implemented by many local governments, leading to a declining trend of laboratory‐confirmed cases in the first four waves 7, 8, 9, 10, 11. However, an unprecedented outbreak of human infection with avian influenza A(H7N9) virus, identified as the fifth wave, occurred in China from September 2016, and a number of cases reported in the fifth wave exceeded those reported in the previous waves in China 8, 9, 10, 12…”
Section: Introductionmentioning
confidence: 99%